Outcomes of surgical management of intracerebral hemorrhagic stroke at a tertiary care center in Yogyakarta, Indonesia - Rahmat Andi Hartanto; Teuku Jauhardin (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Hemorrhagic stroke remains a significant cause of morbidity and mortality worldwide. However, the role of surgical treatment for hemorrhagic stroke remains controversial. Previous studies had proposed surgery can prevent herniation, lowering intracranial pressure (ICP) and reducing mass effect and cellular toxicity. Outcome in previous studies are conflicting. Studies concerning outcomes of surgical management of hemorrhagic stroke in Indonesia are limited. This study aimed to compare the outcome of hemorrhagic stroke treatment between surgical evacuation and conservative management in Dr. Sardjito General Hospital, Yogyakarta, Indonesia. Retrospective cohort study was conducted. Eighty spontaneous intracerebral hemorrhagic (ICH) stroke patients involved in this study during January 2014 to August 2015. Of whom 36 (45%) male and 44 (55%) female. There were 45 and 35 patients underwent surgical treatment and conservative management, respectively. Surgical treatment group survival was 74%, whereas the survival in the conservative group was 26%. There was a statistically significant difference between surgery group and conservative group (p